Allegoric Interpretations of Ancient Myths in Old Polish Literature - Wichowa, Maria (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
Allegory is about seeing a double meaning in a work of art. In this particular text, literal and hidden meaning has a long history of both practical use in creating utterances and creating theories of pictorial communication. In the Old Polish era, the most representative examples of allegorical reading of myths are Andrzej Zbylitowski’s Renaissance translation of the story of Acteon from Ovid’s Metamorphoses and Walerian Otwinowski’ commentary in his translation of this work, which he intended to be used by students. Therefore, in the explanations placed on the margins of the translated text, he extracted the myth’s moral, theological, and philosophical truths. He also made an allegory of a Christianization of “pagan” beliefs, treating them as stories about false gods, under which the authors passed on knowledge about the Christian God, probably under his inspiration, because they did not know the Bible.